Impact of Financial Inclusion for Welfare : Analyze to Household Level - Addury, Multazam Mansyur (Journal of Finance and Islamic Banking, 2018)
One indicator of poverty in a country is still low access to financial facilities to the community. Therefore, a program of massive financial inclusion is currently being campaigned. Financial inclusion is a program that provides easy access to finance (savings and financing) to the community so that it can improve welfare. This study analyzes the part of financial inclusion, namely the influence of the amount of credit and deposits/investments on household income, household consumption expenditure, and household living facilities. The data is taken from the Indonesian Family Life Survey in the period 2000, 2007 and 2014. This research uses panel data regression analysis. The results of the study found that (a) there is a significant effect of the amount of credit on household income, (b) there is a significant influence on the amount of credit and savings/investments on household consumption expenditures, and (c) there is no significant effect on the amount of credit and savings or investment household residence facilities.